Genetic parameters and genotype-environment interaction in clonal trials of Cedrela odorata L. - Olvera-Moreno, Susana; López-Upton , Javier; Sánchez-Monsalvo, Vicente; Jiménez-Casas , Marcos (Instituto de Ecología, A.C., 2022)
To increase the productivity of commercial plantations, it is necessary to carry out genetic improvement activities, for which it is necessary to estimate genetic parameters. In Mexico, superior growth clones of Cedrela odorata L. have been generated that require evaluation under various environmental conditions. The objective was to estimate heritability, genetic and phenotypic correlation and genotype-environment interaction of 14 morphological and growth characters of C. odorata in two clonal trials at seven years. Clones were grafted at the age of four months. Ninety clones planted in two different environments, Isla, Veracruz and San Francisco, Campeche, were evaluated. In Isla 12 heritability values were higher. The highest heritabilities at both sites were estimated for petiolule length, volume, and stem diameter. Phenotypic and genetic correlations between growth traits were high and positive, but between growth traits and stem, crown, and leaf traits, they were low to moderate. The volume used as selection criterion would not negatively affect the response of any of the variables evaluated. Despite the environmental differences, high stability was determined in the behavior of the selected clones, except for four higher volume interactive clones in San Francisco. With the exclusion of three of the most interactive clones for volume, the genotype-environment interaction of this characteristic is almost totally reduced. Thus, to avoid genetic loss, it is suggested to use these clones only in Campeche sites, and the other superior ones in both sites.